If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(5 + 2x) = -49 (5 * -7 + 2x * -7) = -49 (-35 + -14x) = -49 Solving -35 + -14x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -14x = -49 + 35 Combine like terms: -35 + 35 = 0 0 + -14x = -49 + 35 -14x = -49 + 35 Combine like terms: -49 + 35 = -14 -14x = -14 Divide each side by '-14'. x = 1 Simplifying x = 1
| 23+129+x=180 | | 4*ln(7x)=8 | | 2z^2-5z+4=0 | | 500x-13=65x-78 | | 6(-4x+7)-12=-7(2x+7) | | b^3+27= | | m^2x^3+m^9x^2+m^3x^4+m^6= | | 5(7+4x)=155 | | y^2+5y=7 | | 4x+3=9x+33 | | -3x+68-7(x-1)=8x-(2x-2)-6x+3 | | 1.05x=9.020 | | 2n+11=17 | | 3x+39=-69+12x | | -7x+18-7(x-3)=4x-(6x-6)8x+9 | | x^2+10c-25=0 | | 16x+2=8x+6 | | 3b^2+3b-6=0 | | n/3-7=5 | | x/5=181 | | 8/5(-3) | | 3b^2+3b+6=0 | | -[3x-(12x+5)]=5+(8x+6) | | r^2-4r=16+2r | | 8x-29=6x-7 | | .35x+1.6=-0.5 | | y-4=8/5(x-3) | | 5x-6=3(x-2)+2x | | 2[x-(4x+10)+4]=2(x+6) | | 98-(4x+12)=4(x+8)+x | | P(x)=x^2-5x+6 | | 23-4x=11-8x |